PERAN PIMPINAN DALAM MENINGKATKAN KINERJA PUSTAKAWAN DI PERPUSTAKAAN MADRASAH ALIYAH NEGERI 2 PONTIANAK - Arif, Ihsanul; Hanum, Atiqa Nur Latifa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis recent study discusses the role of the leader in improving librarian performance at the Library of MAN 2 Pontianak. This study aims to determine the role, efforts, and obstacles faced in improving librarian performance. The method used in this study was qualitative in the form of descriptive research. The data were collected using interviews, observation, and documentation techniques. The informants who took part in the study were the headmaster and the head of the school library. The findings showed that the headmaster plays a significant role in improving the librarians’ performances. The obstacle faced was that librarians are still lacking in discipline. Considering the problem, the alternative way to overcome it is to provide human resources with the educational background of library education to facilitate the processing and management of the library.  Keywords: Librarian roles, Performances, School Library